Blood culture-PCR to optimise typhoid fever diagnosis after controlled human infection identifies frequent asymptomatic cases and evidence of primary bacteraemia. Issue 4 (April 2017) - Darton, Thomas C.; Zhou, Liqing; Blohmke, Christoph J.; Jones, Claire; Waddington, Claire S.; Baker, Stephen; Pollard, Andrew J.
Summary: Background: Improved diagnostics for typhoid are needed; a typhoid controlled human infection model may accelerate their development and translation. Here, we evaluated a blood culture-PCR assay for detecting infection after controlled human infection with S . Typhi and compared test performance with optimally performed blood cultures. Methodology/Principal findings: Culture-PCR amplification of blood samples was performed alongside daily blood culture in 41 participants undergoing typhoid challenge. Study endpoints for typhoid diagnosis (TD) were fever and/or bacteraemia. Overall, 24/41 (59%) participants reached TD, of whom 21/24 (86%) had ≥1 positive blood culture (53/674, 7.9% of all cultures) or 18/24 (75%) had ≥1 positive culture-PCR assay result (57/684, 8.3%). A further five non-bacteraemic participants produced culture-PCR amplicons indicating infection; overall sensitivity/specificity of the assay compared to the study endpoints were 70%/65%. We found no significant difference between blood culture and culture-PCR methods in ability to identify cases (12 mismatching pairs, p = 0.77, binomial test). Clinical and stool culture metadata demonstrated that additional culture-PCR amplification positive individuals likely represented true cases missed by blood culture, suggesting the overall attack rate may be 30/41 (73%) rather than 24/41 (59%). Several participants had positive culture-PCR results soon after ingesting challenge providing new evidence for occurrence of an early primary bacteraemia. Conclusions/Significance: Overall the culture-PCR assay performed well, identifying extra typhoid cases compared with routine blood culture alone. Despite limitations to widespread field-use, the benefits of increased diagnostic yield, reduced blood volume and faster turn-around-time, suggest that this assay could enhance laboratory typhoid diagnostics in research applications and high-incidence settings. Graphical abstract: The culture-PCR assay for detection of fliC- D DNA in human blood samples. Highlights: Culture in ox-bile/tryptone soy broth selectively enriches for bile-tolerant Salmonella Typhi while lysing human cells. PCR sensitivity for detecting typhoid in clinical blood is limited by very low level bacteraemia during clinical illness. PCR amplification of S. Typhi fliC -d in pre-cultured blood can accurately identify typhoid infection in challenge study participants. Daily culture-PCR of blood collected from challenge study participants suggests primary bacteraemia occurs 12–36 h after S. Typhi ingestion. Additional use of culture-PCR demonstrates the true attack rate after typhoid challenge is markedly higher (75%) than previously assumed (60%).